Color confinement and dual superconductivity in unquenched QCD - Biagio Lucini (Nuclear Physics A, 2002)
We report on evidence from lattice simulations that confinement is produced by dual superconductivity of the vacuum in full QCD as in quenched QCD. Preliminary information is obtained on the order of the deconfining phase transition.